Intrahepatic cholestasis of pregnancy can increase the risk of metabolic disorders: A Meta-Analysis focusing on Pregnancy Population - Zhang, LeiYing; Tang, Chen; Ye, ChenLian; Huang, LuRen; Wu, Yan (Journal of Medical Biochemistry, 2022)
Background: Gestational diabetes mellitus (GDM) and preeclampsia (PE) as one of the common complications during pregnancy, Studies indicated that abnormal bile acid metabolism is related to its pathogenesis. Intrahepatic cholestasis of pregnancy (ICP) is the most common pregnancy-specific liver disease,which classic symptoms include generalized pruritus that commonly, and biochemical evidence of elevated bile acids.Our study aimed to explore the correlation between the ICP  presence and risk of GDM,PE incident in pregnant women. Methods: A meta-analysis, which included 10 eligible studies including 17,688 ICP cases and 1,386,771 controls, is performed to assess the correlation of ICP with preeclampsia (PE) and gestational diabetes mellitus (GDM). There are 7 studies to investigate the relationship between ICP and PE, and 9 studies for evaluating the relationship between ICP and GDM. All eligible studies are screened from Pubmed, Web of science and EBSCO database.Results: The results of this meta-analysis indicate that ICP significantly increase the risk for both PE (pooled odds ratio [OR]: 2.56 [95%CI: 2.27~2.88], I2 heterogeneity = 35%, p heterogeneity = 0.16) and GDM (pooled OR: 2.28 [95%CI: 1.69~3.07], I2 heterogeneity = 81%, p heterogeneity < 0.001). In the sensitivity analysis of GDM, excluding the largest heterogeneity study can not change the result (pooled OR: 2.86 [95%CI: 2.59~3.16], I2 heterogeneity = 0%, p heterogeneity = 0.56).Conclusions: This meta-analysis shows that ICP is closely associated with ICP inceased risk of PE and GDM) during pregnancy.
Keywords: intrahepatic cholestasis of pregnancy; preeclampsia; gestational diabetes mellitus